2012
DOI: 10.1016/j.jmb.2012.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Target Binding to S100B Reduces Dynamic Properties and Increases Ca2+-Binding Affinity for Wild Type and EF-Hand Mutant Proteins

Abstract: Mutations in the second EF-hand (D61N, D63N, D65N, E72A) of S100B were used to study its Ca2+-binding and dynamic properties in the absence and presence of abound target, TRTK-12. With D63NS100B as an exception (D63NKD = 50 ± 9 µM), Ca2+-binding to EF2-hand mutants were reduced by more than 8-fold in the absence of TRTK-12 (D61NKD = 412 ± 67 µM; D65NKD = 968 ± 171 µM; E72AKD = 471 ± 133 µM), when compared to wild-type protein (WTKD = 56 ± 9 µM). For the TRTK-12 complexes, the Ca2+-binding affinity to wild type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(68 citation statements)
references
References 63 publications
7
52
0
9
Order By: Relevance
“…In this regard, we examined whether this small peptide was sufficient to induce what is termed the “final folding” event that occurs upon S100 protein-target complex formation [6]. We examined whether conformational exchange in S100A4, which is observed in the absence of bound target, could be stabilized upon binding the MIIA 1908-1923 peptide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, we examined whether this small peptide was sufficient to induce what is termed the “final folding” event that occurs upon S100 protein-target complex formation [6]. We examined whether conformational exchange in S100A4, which is observed in the absence of bound target, could be stabilized upon binding the MIIA 1908-1923 peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with other S100 proteins suggest that the increased Ca 2+ -binding affinity observed in the presence of target is due to a ligand-induced reduction in S100 backbone and side chain dynamics [5,6]. Localized target-mediated enhancement of the S100A4/Ca 2+ interaction would permit high intracellular S100A4 expression levels (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As previously shown, calcium-bound S100B is dynamic at multiple time scales (nanoseconds–milliseconds) [6264] and upon binding a molecular target, S100B becomes less dynamic and is able to achieve a more stable conformation (i.e., extension of helix 4 and 4′) [62]. In general, calcium-loaded S100B has fast and slow time scale motions in back bone amides found in the hinge region, helix 3 and helix 4 (i.e., hydro phobic pocket), which are essential for S100–target binding.…”
Section: Future Perspectivementioning
confidence: 99%
“…However, another explanation is that the Ca 2ϩ binding affinity of S100 proteins can also be increased upon binding other metals and/or their physiologically relevant protein target(s). For example, it is well established in vitro that the affinity of S100B and other S100 proteins for Ca 2ϩ is increased after Zn 2ϩ binding (48,49), redox modification of critical cysteine residues (50), and/or by target binding, although the mechanism by which Ca 2ϩ binding is increased by as much as 200-fold upon target binding to S100B is still under investigation (18,(51)(52)(53).…”
Section: Camentioning
confidence: 99%